Effects of Calcium, Vitamin D, and Hormone Therapy on Cardiovascular Disease Risk Factors in the Women's Health Initiative: A Randomized Controlled Trial. Issue 1 (January 2017) - Schnatz, Peter F.; Jiang, Xuezhi; Aragaki, Aaron K.; Nudy, Matthew; O'Sullivan, David M.; Williams, Mark; LeBlanc, Erin S.; Martin, Lisa W.; Manson, JoAnn E.; Shikany, James M.; Johnson, Karen C.; Stefanick, Marcia L.; et al.
Abstract : OBJECTIVE: To analyze the treatment effect of calcium+vitamin D supplementation, hormone therapy, both, and neither on cardiovascular disease risk factors. METHODS: We conducted a prospective, randomized, double-blind, placebo-controlled trial among Women's Health Initiative (WHI) participants. The predefined primary outcome was low-density lipoprotein cholesterol (LDL-C). RESULTS: Between September 1993 and October 1998, a total of 68, 132 women aged 50–79 years were recruited and randomized to the WHI–Dietary Modification (n=48, 835) and WHI–Hormone Therapy trials (n=27, 347). Subsequently, 36, 282 women from WHI–Hormone Therapy (16, 089) and WHI–Dietary Modification (n=25, 210) trials were randomized in the WHI–Calcium+Vitamin D trial to 1, 000 mg elemental calcium carbonate plus 400 international units vitamin D3 daily or placebo. Our study group included 1, 521 women who participated in both the hormone therapy and calcium+vitamin D trials and were in the 6% subsample of trial participants with blood sample collections at baseline and years 1, 3, and 6. The average treatment effect with 95% confidence interval, for LDL-C, compared with placebo, was −1.6, (95% confidence interval [CI] −5.5 to 2.2) mg/dL for calcium+vitamin D alone, −9.0 (95% CI −13.0 to −5.1) mg/dL for hormone therapy alone, and −13.8 (95% CI −17.8 to −9.8) mg/dL for the combination. There was no evidence of a synergistic effect of calcium+vitamin D+hormone therapy on LDL-C ( P value for interaction=.26) except in those with low total intakes of vitamin D, for whom there was a significant synergistic effect on LDL ( P value for interaction=.03). CONCLUSION: Reductions in LDL-C were greater among women randomized to both calcium+vitamin D and hormone therapy than for those randomized to either intervention alone or to placebo. The treatment effect observed in the calcium+vitamin D+hormone therapy combination group may be additive rather than synergistic. For clinicians and patients deciding to begin calcium+vitamin D supplementation, current use of hormone therapy should not influence that decision. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00000611. Abstract : Supplemental Digital Content is Available in the Text.Additive effects (both positive and some negative) on multiple cardiovascular disease risk factors were observed when menopausal women were randomized to both calcium and vitamin D and hormone therapy.